Potential for cryopreservation of three rattan species in liquid nitrogen - Hor, Y.L. (Universiti Putra Malaysia, 2014)
This study evaluates the potentiality for cryopreservation of excised embryos of three rattan species, namely, Calamus caesius, C. erinaceus and C. subinermis. Embryos of all three species showed differential response on exposure to liquid nitrogen (LN), suggesting considerable physiological diversity within the genus. Of the three species, C. caesius shows the best potential for cryopreservation with 82% viability after LN exposure followed by C. erinaceus with 63% viability. C. subinermis was relatively difficult to cryopreserve with only 25% viability after LN exposure. In all cases, best viability was obtained following desiccation to moisture contents below 10%, except for C. caesius where it was only desiccated up to around 28% moisture.